Reactive oxide species-scavenging lipid-polymer nanoparticles for neuroprotection after spinal cord injury. (September 2021) - Zhang, Tianhui; Lin, Feng; Liu, Wanguo; Liu, Yixuan; Guo, Zhihui; Xiao, Chunsheng; Zhuang, Xiuli; Chen, Xuesi
Highlights: A ROS responsive polymer, poly(PMT-co-EGDM), was synthesized and used to construct ROS-scavenging lipid-polymer nanoparticles (PELPNPs). PELPNPs exhibited a good ROS-scavenging ability both in vitro and in vivo . PELPNPs could reduce the ROS-induced inflammation and protect neurons against oxidative damages. PELPNPs reduced the secondary injury and promoted functional recovery in a rat contusion injury model. Abstract: Suppression of secondary damage following traumatic spinal cord injury (SCI) remains a great challenge in the clinical treatment of acute SCI. To date, the most validated treatment in clinic is the use of antioxidants to reduce reactive oxygen species (ROS)-induced oxidative damage during the secondary injury process. However, clinically available antioxidants, such as methylprednisolone, commonly lead to modest improvement in neurological recovery and yet are accompanied with serious side effects. Herein, we report on the development of lipid-polymer nanoparticles (denoted as PELPNPs) with a high ROS-scavenging ability that effectively eliminated ROS and thus reduced long-term secondary injury in a clinically relevant rat SCI model. In vitro tests demonstrated that PELPNPs could readily scavenge overproduced ROS, reduce inflammation, and protect glial cells and neurons against H2 O2 -induced oxidative damage. After intravenous administration, PELPNPs significantly improved the recovery of locomotor function and reduced the lesion area through effective protection of neurons and myelin sheaths. Mechanism studies proved that the superior therapeutic effect of PELPNPs was attributed to their high ROS scavenging and anti-inflammatory abilities. Thus, the proposed ROS-scavenging nanoparticle system shows promise for effective treatment of clinical SCI. Graphical abstract: Image, graphical abstract